Epigenetics and Dermatology. - Lu, Qianjin (Elsevier Science, 2015)
Epigenetics and Dermatology explores the role of epigenetics in the pathogenesis of autoimmune-related skin diseases and skin cancer. Leading contributors cover common and uncommon skin conditions in which extensive epigenetic research has been done. They explain how environmental exposures (chemicals, drugs, sunlight, diet, stress, smoking, infection, etc.) in all stages of life (from a fetus in-utero to an elderly person) may result in epigenetic changes that lead to development of some skin diseases in life. They also discuss the possibilities of new and emergent epigenetic treatments whic.